2021
DOI: 10.3389/fcell.2021.707607
|View full text |Cite
|
Sign up to set email alerts
|

AAV-Containing Exosomes as a Novel Vector for Improved Gene Delivery to Lung Cancer Cells

Abstract: Lung carcinoma is the most common type of cancer and the leading cause of cancer-related death worldwide. Among the numerous therapeutic strategies for the treatment of lung cancer, adeno-associated virus (AAV)-mediated gene transfer has been demonstrated to have the potential to effectively suppress tumor growth or reverse the progression of the disease in a number of preclinical studies. AAV vector has a safety profile; however, the relatively low delivery efficacy to particular subtypes of lung carcinoma ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…In fact, clinical trials using genome editing have been discontinued because of suspicion of the development of chromosomal abnormalities. Therefore, as one of the novel gene therapy strategies, a drug delivery system for the AAV-encapsulating EV, which contains the AAV vector within the EV, was reported to be useful in the intervention of various target tissues in some diseases [189][190][191][192][193][194][195][196][197][198][199][200]. Furthermore, the effectiveness of gene therapy with AAV vectors is greatly affected by neutralizing antibodies [81,[201][202][203].…”
Section: Adeno-associated Virus (Aav)-encapsulating Evsmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, clinical trials using genome editing have been discontinued because of suspicion of the development of chromosomal abnormalities. Therefore, as one of the novel gene therapy strategies, a drug delivery system for the AAV-encapsulating EV, which contains the AAV vector within the EV, was reported to be useful in the intervention of various target tissues in some diseases [189][190][191][192][193][194][195][196][197][198][199][200]. Furthermore, the effectiveness of gene therapy with AAV vectors is greatly affected by neutralizing antibodies [81,[201][202][203].…”
Section: Adeno-associated Virus (Aav)-encapsulating Evsmentioning
confidence: 99%
“…Therefore, the induction of immune tolerance to AAV vectors has become an important issue for efficient and safe gene transduction. Nevertheless, it is possible to induce a reduction in immunogenicity to the AAV vector by encapsulating the AAV vector within EVs, which is naturally present in the body (as a natural transporter); it is expected that AAV vector transduction is more efficient than AAV vector administration alone [189,194,204]. In addition, AAV vectors administrated in vivo are consumed by innate immunity plasmacytoid dendritic cells, as mediated by Toll-like receptor 9 [205].…”
Section: Adeno-associated Virus (Aav)-encapsulating Evsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the safety and efficacy of AAV vectors need to be improved due to the occurrence of deaths in clinical trials caused by single high-dose administration, imperfect organ orientation, or the presence of neutralizing antibodies of AAV vectors that bind to the AAV capsid and inhibit the interaction with target cells, resulting in a reduction of AAV-transduction efficacy, which is a major clinical barrier. Previously, it was reported that AAV is naturally secreted via the interior or surface of EVs into the extracellular space in two types of forms, EV-encapsulated or EV-associated AAVs (EV-AAVs), which can be taken up with high transduction efficacy by target cells [177][178][179][180][181][182][183][184]. Furthermore, the EV-AAV vector can be protected from neutralizing antibodies in vivo and in vitro compared to non-encapsulated or associated AAVs [185,186].…”
Section: Ev-encapsulated Adeno-associated Virusmentioning
confidence: 99%
“…Moreover, it displays impressive resistance to antibody neutralization. This suggested that a new vector can be created using exosomes that include AAV to enhance the gene transfer in lung cancer cells ( 43 ). Since the presence of the blood brain barrier is a challenge in the treatment of central nervous system diseases, Chen et al hypothesized that the AAV vector may be an excellent gene delivery mechanism for treating central nervous system diseases ( 44 ).…”
Section: Aav and Cancermentioning
confidence: 99%